Barriers and Facilitators of Exercise Rehabilitation in Patients With Myocardial Infarction Based on an Updated Consolidated Framework for Implementation Research: A Systematic Review - Ya Wang; Hualian Pei; Junjun Luo; Minfang Guan; Wenjing Sun; Hongxing Wang; Qinhong Xu (Reviews in Cardiovascular Medicine)
Background: Rehabilitation through exercise is the core content of cardiac rehabilitation, which is conducive to promoting myocardial recovery and reducing mortality. However, the overall participation rate in exercise rehabilitation is low. Thus, this study aimed to comprehensively evaluate the barriers and facilitators of exercise rehabilitation for patients with myocardial infarction using the updated Consolidated Framework for Implementation Research (CFIR 2.0). Methods: Systematic research retrieval was reviewed via PubMed, Embase, Web of Science, Cochrane Library, ProQuest, and PsycINFO databases. Based on CFIR 2.0, this study used descriptive analyses to analyze the research results of each included document and identify it as a barrier or facilitator. Results: In total, 5185 studies were obtained from a preliminary search; 11 studies were ultimately included; 5 studies were quantitative. This study summarized 50 influencing factors, including 27 barriers and 23 facilitators. Most factors were related to the individual domain (64%). The remaining factors were related to the inner setting domain (20%), innovation domain (10%), implementation process domain (4%), and outer setting domain (2%). Conclusions: This study integrated the barriers and facilitators of exercise rehabilitation of patients with myocardial infarction. The study emphasizes the importance of considering the individual domain, inner setting domain, innovation domain, implementation process domain, and outer setting domain factors when implementing exercise rehabilitation. This study provides a systematic foundation for optimizing cardiac rehabilitation programs. The PROSPERO Registration: CRD42024521287, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024521287.